Immunoglobulin G4-Related Spinal Intramedullary Inflammatory Pseudotumor: A Case Report and Literature Review - Qi, Zhou; Liu, Jianli; Li, Guoqiang; Zhang, Yinian (Frontiers in Neurology, 2022)
Immunoglobulin G4-related disease (IgG4-RD) is a series of specific autoimmune diseases affecting a large number of organs. Inflammatory pseudotumor is a histologically proven benign tumor–like lesion that most commonly involves the lung and the orbit, which is rare in the central nervous system and is the rarest in the spinal canal. In this report, we provided a case of IgG4-related intramedullary spinal inflammatory pseudotumor and a literature review. A 29-year-old man was transferred to the department of neurosurgery of Lanzhou University Second Hospital with progressing progressive quadriparesis after numbness and weakness of both lower limbs for 50 days. Enhanced magnetic resonance imaging (MRI) of the spine revealed an isointense signal on T1-weighted images and hyperintense signal on T2-weighted images from an enhanced mass located at the thoracic (9-10) vertebrae region, for which a schwannoma was highly suspected. Then, a posterior median approach was adopted and the lesion was gross total resected. The patient accepted further glucocorticoids after the diagnosis of an IgG4-related inflammatory pseudotumor was made, and the patient’s symptoms, such as quadriparesis and lower limb weakness, improved. This case highlights the importance of considering IgG4-related inflammatory pseudotumors as a differential diagnosis in patients with lesions involving the spinal intramedullary along with lower limb weakness when other more threatening causes have been excluded. IgG4-related inflammatory pseudotumors are etiologically enigmatic and unpredictable, imaging of differential diagnosis of IgG4-related inflammatory pseudotumor is very hard due to the resemblance to malignant tumors, and total resection might not be warranted. Glucocorticoids and surgery are usually the first line of treatment and diagnosis.